ARchitect: advancing architectural visualization and interaction through handheld augmented reality - Israr, Sabahat; Khan, Mudassar Ali; Anwar, Muhammad Shahid; Awan, Kamran Ahmad; Mahfoudh, Saoucene; Althaqafi, Turki; Alhalabi, Wadee (Frontiers in Virtual Reality, 2025)
The architecture, engineering, and construction industry requires enhanced tools for efficient collaboration and user-centric designs. Traditional visualization methods relying on 2D/3D CAD models often fall short of modern demands for interactivity and context-aware representation. To address this limitation, this study introduces ARchitect, a mobile-based markerless augmented reality (AR) framework aimed at revolutionizing architectural artifact visualization and interaction. The proposed approach enables users to dynamically overlay and manipulate 3D architectural elements, such as roofs, windows, and doors, within their physical environment using AR raycasting and device sensors. Algorithms supporting translation, rotation, and scaling allow precise adjustments to model placement while integrating metadata to enhance design comprehension. Real-time lighting adaptation ensures seamless environmental blending, and the framework’s usability is quantitatively evaluated using the Handheld Augmented Reality Usability Scale (HARUS). ARchitect achieved a usability score of 89.2, demonstrating significant improvements in user engagement, accuracy, and decision-making compared to conventional methods.